Research and application of gas lift technology in bedrock gas reservoirs -A case study of Jianbei gas reservoir - Li, ZhanChun; Yang, Zhi; Chen, YuHui; Tan, XiaoHua; He, ZhenTao; He, WenFa (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
The Jianbei gas reservoir, situated in the Altun Mountains of the Qaidam Basin, is a typical bedrock gas reservoir. Since its commissioning, the gas wells have generally encountered water breakthrough, leading to a significant drop in production. To address this issue, a pressurised gas lift process was implemented to drain water and boost production. While most wells exhibited positive production increases, some showed little to no change in productivity post-treatment. Therefore, it is imperative to investigate the reasons for these discrepancies and adjust/upgrade the original plan accordingly. Through comprehensive analysis from various perspectives, including fluid accumulation issues, the gas lift process itself, and wellbore structure, it was identified that the primary factors limiting the effectiveness of gas lift in the Jianbei gas reservoir are severe fluid accumulation in the wellbore, poor adaptability of the gas lift process in certain wells, inappropriate tubing size, and severe formation damage. To tackle these issues, the gas lift plan for the Jianbei gas reservoir was upgraded and optimised. Relevant parameters were redesigned based on tubing diameter optimization principles and gas lift characteristic curves, aiming to maximize the stimulation effect of gas lift. This approach effectively resolves the existing technical challenges and provides a solid scientific foundation and technical support for future gas reservoir management and development, ensuring optimal operation of the gas wells.